Personality traits as predictors of OCD remission: A longitudinal study - Law, Clara; Kamarsu, Snigdha; Obisie-Orlu, Immanuela C.; Belli, Gina M.; Mancebo, Maria; Eisen, Jane; Rasmussen, Steven; Boisseau, Christina L. (Journal of affective disorders, 2023)
Personality traits may confer vulnerability to psychopathology. However, few studies have examined the association between personality traits and obsessive-compulsive disorder (OCD) course. The present study investigates personality traits, OCD symptom severity, and illness duration as a predictor of OCD remission. 166 treatment-seeking adults with OCD, recruited as part of the Brown Longitudinal Obsessive-Compulsive Study, completed the NEO Five-Factor Inventory 3 (NEO-FFI) and were in episode for OCD at time of NEO-FFI completion. Participants were followed for up to 3 years. Results suggest individuals with OCD had a 21 % likelihood of reaching remission over the course of 3 years. Greater OCD symptom severity and longer illness duration were associated with a decreased likelihood of remission. Among the five factors of personality, only low extraversion was associated with a decreased rate of remission. Neuroticism, openness, agreeableness, and conscientiousness were not associated with remission. As this was an observational study, treatment was not controlled precluding examination of treatment on course. Further, data collected on age of onset and symptom severity during follow up were retrospective and therefore are also subject to recall bias. Our findings provide preliminary support that personality traits are potential factors impacting course and symptom presentation. Future research is necessary to determine the mechanisms in which personality traits may influence the presentation and course of OCD. •Examined the impact personality traits on OCD symptom severity and remission•Neuroticism, extraversion, and conscientiousness are associated with symptom severity.•Those with OCD had a 21 % likelihood of reaching remission across 3 years.•Low extraversion and greater OCD symptom severity decrease the likelihood of remission.